Transportation Sustainability Follows From More People in Fewer Vehicles, Not Necessarily Automation. Issue 4 (2nd October 2019) - Merlin, Louis A.
Abstract: Shared mobility and ride-hailing have not apparently promoted transportation sustainability to date. Evidence suggests ride-hailing increases congestion and primarily serves the advantaged, and services that encourage pooled rides have not taken off. However, simulation research into automated vehicle ride-hailing systems indicates greater ride pooling may be the key to major improvements in transportation sustainability. Though the results are widely varying, the common finding is pooled ride mobility systems could offer substantial benefits if they are able to attain sufficient market share. Moreover, such systems do not require self-driving vehicles but merely centralized fleet coordination, achievable with today's technologies.